Molecular mechanism and therapeutic modulation of high mobility group box 1 release and action: an updated review. (June 2014) - Lu, Ben; Wang, Ce; Wang, Mao; Li, Wei; Chen, Fangping; Tracey, Kevin J; Wang, Haichao
<x xml:space="preserve">Abstract</x> High mobility group box 1 (HMGB1) is an evolutionarily conserved protein, and is constitutively expressed in virtually all types of cells. Infection and injury converge on common inflammatory responses that are mediated by HMGB1 secreted from immunologically activated immune cells or passively released from pathologically damaged cells. Herein we review the emerging molecular mechanisms underlying the regulation of pathogen-associated molecular patterns (PAMPs)-induced HMGB1 secretion, and summarize many HMGB1-targeting therapeutic strategies for the treatment of infection- and injury-elicited inflammatory diseases. It may well be possible to develop strategies that specifically attenuate damage-associated molecular patterns (DAMPs)-mediated inflammatory responses without compromising the PAMPs-mediated innate immunity for the clinical management of infection- and injury-elicited inflammatory diseases.